Author Correction: Global geochemical fingerprinting of plume intensity suggests coupling with the supercontinent cycle - Gamal El Dien, Hamed; Doucet, Luc; Li, Zheng-Xiang; Cox, Grant; Mitchell, Ross (NATURE PUBLISHING GROUP, 2020)
The original version of this Article omitted from the author list the 4th and 5th authors, Grant Cox and Ross Mitchell, who were both at Curtin University. Consequently, the corrected version of the Acknowledgements removes the following from the original version: ‘and Ross Mitchell’. In addition, the following was added to the Author Contributions: ‘G.M.C. and R.M. were involved in an early attempt of this study.’. This has been corrected in both the PDF and HTML versions of the Article.